Acute pancreatitis: a review of etiology, diagnosis and management of local complications - Szczerek, Emilia; Płóciniczak, Viktoria (Quality in Sport, 2025)
Background: Acute pancreatitis (AP) is an inflammatory disease primarily caused by gallstones and alcohol consumption. Its clinical presentation varies significantly, ranging from mild interstitial edematous pancreatitis to severe necrotizing forms. The Revised Atlanta Classification establishes the standard for defining the severity of the disease and categorizing its local complications into four distinct types: acute peripancreatic fluid collections (APFC), acute necrotic collections (ANC), pancreatic pseudocysts, and walled-off necrosis (WON). Aim: The aim of this study was to review the current literature regarding the epidemiology, pathophysiology, diagnostic criteria, and management strategies for the local complications of acute pancreatitis. Materials and Methods: The review included scientific papers sourced from the PubMed and Google Scholar databases. Results: The diagnosis and characterization of local complications rely heavily on imaging modalities. While Contrast-Enhanced Computed Tomography remains the standard tool, Magnetic Resonance Imaging and Endoscopic Ultrasound demonstrate superior accuracy in detecting solid necrotic debris. Distinguishing between fluid-only collections (APFC, pseudocyst) and those containing necrosis (ANC, WON) is critical, as it dictates the therapeutic approach. The review highlights that while APFCs often resolve spontaneously, necrotic collections carry a higher risk of infection and mortality. Management strategies have evolved significantly, moving away from open surgery toward minimally invasive methods. Conclusions: Accurate classification of local complications based on the Revised Atlanta Classification is essential for guiding clinical decision-making. Contemporary management of AP complications favors a "step-up" approach, prioritizing conservative treatment and minimally invasive endoscopic interventions over traditional surgical necrosectomy to reduce morbidity and improve patient outcomes.